2018
DOI: 10.3766/jaaa.16126
|View full text |Cite
|
Sign up to set email alerts
|

Speech Understanding and Sound Source Localization by Cochlear Implant Listeners Using a Pinna-Effect Imitating Microphone and an Adaptive Beamformer

Abstract: The data support the use of the natural microphone setting as a default setting. The natural setting (1) provides better speech understanding in noise than the omni setting, (2) does not impair sound source localization, and (3) retains low-frequency sensitivity to signals from the rear. Moreover, bilateral CIs equipped with adaptive beamforming technology can engender speech understanding scores in noise that fall only a little short of scores for a single CI in quiet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…By contrast, at the 65-dB noise level, performance was much better for signals presented from the front than from the back. Relative to scores in the 55 dB condition, where the microphones were in omni mode, in 65 dB noise, performance for speech from the front improved by 25% points-a gain similar to that we have reported previously for beamformers in our simulation of a restaurant (Dorman et al, 2018). At the same time, relative to scores in the 55-dB condition, scores for speech from the back decreased by 17% points.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…By contrast, at the 65-dB noise level, performance was much better for signals presented from the front than from the back. Relative to scores in the 55 dB condition, where the microphones were in omni mode, in 65 dB noise, performance for speech from the front improved by 25% points-a gain similar to that we have reported previously for beamformers in our simulation of a restaurant (Dorman et al, 2018). At the same time, relative to scores in the 55-dB condition, scores for speech from the back decreased by 17% points.…”
Section: Discussionsupporting
confidence: 85%
“…By reducing signal inputs from off the frontal axis, these systems improve the signal-to-noise ratio (SNR) and improve speech understanding in noise. In a previous experiment, using a simulation of a restaurant with a semidiffuse noise field, we found improvements of 20-30% points for patients fit with monaural and bilateral beamformers (Dorman et al, 2018).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Cochlear implant (CI) users wearing audio processors for which the microphone is placed behind the ear are not able to utilize pinna cues, which may result in poor localization performance. It has been demonstrated that artificial imitation of the pinna effect in the form of frequency-dependent microphone directionality improves speech intelligibility in noise of CI users (Chung et al 2004;Kordus et al 2015;Wimmer et al 2016;Honeder et al 2018;Dorman et al 2018). In contrast, only limited data for the localization performance of bilateral cochlear implant (BiCI) users with pinna imitation algorithms are available.…”
Section: Introductionmentioning
confidence: 99%
“…When the SONNET audio processor (MED-EL) was introduced in 2014, it became our audio processor of choice, partly because it has microphone directionality settings designed to improve users' speech understanding in noise and sound localization abilities. And indeed, the SONNET has been shown to improve speech understanding in challenging situations, improve sound quality, and increase user satisfaction [13][14][15][16]. These studies, however, were conducted on CI users (unilateral or bilateral) with bilateral severe-to-profound hearing loss or on CI/EAS (electric acoustic stimulation) users-not, to the best of our knowledge, on a group of CI users with SSD.…”
Section: Introductionmentioning
confidence: 97%